REDESIGN AND CREATION OF THE CROCKING MACHINE FABRIC LOCK FOR MORE ACCURATE CROCKING - Reza Tripratama Budiono; Basuki, Puji (Nacreva Publisher, 2025)
This study aims to redesign the fabric locking system on a crocking machine to address the main problem, namely how to create a more stable and accurate locking system in the fabric colorfastness testing process. The research methods include literature study, design, prototype creation, and experiential testing. The results show that the old locking system with 2 bolts requires an average of 28 seconds for installation, testing, and removal, but produces less stable clamping and the fabric tends to wrinkle. Meanwhile, the new locking system with 4 bolts requires 46 seconds, but is able to provide a stronger, more stable, and more accurate clamping without causing wrinkling. Tests on various types of fabrics such as cotton combed 24s, poly span rib, and DTY brush light weight can prove that the new design is more consistent in maintaining fabric stability during testing. Although it requires longer installation and removal times, the new locking system is proven to improve test results, improve fabric clamping quality, and reduce the risk of machine damage. This design is recommended for application in the textile industry to improve the quality of colorfastness testing and product quality consistency.